Penerapan Model Problem Based Learning Terhadap Sikap Kerjasama Peserta Didik Kelas V SDN Pandeanlamper 04 - Yofi Ninda Pratiwi; Ferina Agustini; Ismartiningsih (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research contains the application of the problem based learning model to the cooperative attitudes of class V students at SDN Pandeanlamper 04, . During the learning process, the teacher asks students to work together in groups. Learning models that can be applied to make learning more innovative and refer to problem solving include the problem based learning model, which is learning by presenting problems by asking questions and facilitating dialogue. The aim of this research is to determine the application of the problem based learning model to the cooperative attitudes of class V students at SDN Pandeanlamper 04. This research uses qualitative methods. The results of this research are the application of the problem based learning model to the cooperative attitudes of students in class V at SDN Pandeanlamper 04. The focus of the research consists of the application of the problem based learning model and students' cooperative abilities. The research setting took place at SDN Pandeanlamper 04 with research subjects consisting of teachers and 26 class V students, consisting of 13 men and 13 women. Data collection techniques use observation, interviews and documentation, while data analysis is descriptive qualitative analysis.